1998
DOI: 10.1029/1998gl900112
|View full text |Cite
|
Sign up to set email alerts
|

Control of Jovian radio emission by Ganymede

Abstract: Abstract. Galileo has been in orbit around Jupiter since December 1995. We present the results of a survey of the data for the frequency range 3.2 MHz to 5.6 MHz, the low-frequency decametric (DAM) emissions. While the control of a portion of the radio emission by the moon Io is well-known, we report that a small but significant portion of low-frequency DAM emission is seen to be correlated with the orbital phase of Ganymede. This result is in agreement with other recent results indicating a significant intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
2
25
0
1
Order By: Relevance
“…Confirmation of the physical origin of these peaks comes from the fact that, when the contents of the white boxes of Figures 4a,b is plotted versus the longitude of Ganymede Λ Ga , they gather in a single broad region in Λ Ga (Figure 4e) that coincides with the higher half of the distributions of Io emissions versus Λ Io (Figure 2c). The peaks in Figures 4c and 4d match the maxima found in Galileo data by Menietti et al [1998] and Hospodarsky et al [2001], but they have a much better signal-to-noise ratio and characterize in greater details the occurrence of the emission, as further illustrated by Figures 4a,b. Also, emission events attributed to the Ganymede-Jupiter interaction are individually identified, allowing us to study their dynamic spectrum, polarization, hemisphere and limb of origin, and compare them to magnetic field models [e.g.…”
Section: Ganymedesupporting
confidence: 70%
See 1 more Smart Citation
“…Confirmation of the physical origin of these peaks comes from the fact that, when the contents of the white boxes of Figures 4a,b is plotted versus the longitude of Ganymede Λ Ga , they gather in a single broad region in Λ Ga (Figure 4e) that coincides with the higher half of the distributions of Io emissions versus Λ Io (Figure 2c). The peaks in Figures 4c and 4d match the maxima found in Galileo data by Menietti et al [1998] and Hospodarsky et al [2001], but they have a much better signal-to-noise ratio and characterize in greater details the occurrence of the emission, as further illustrated by Figures 4a,b. Also, emission events attributed to the Ganymede-Jupiter interaction are individually identified, allowing us to study their dynamic spectrum, polarization, hemisphere and limb of origin, and compare them to magnetic field models [e.g.…”
Section: Ganymedesupporting
confidence: 70%
“…It shows up as a nearly sinusoidal modulation of occurrence as a function of Φ Ga (the orbital phase of Ganymede), but is very difficult to identify as regions of the (CML, Φ Ga ) diagram [Menietti et al, 1998;Hospodarsky et al, 2001].…”
Section: Ganymedementioning
confidence: 99%
“…Recent papers have shown that in addition to Io, the satellites Callisto, Ganymede, and Europa show a measurable influence on Jupiter's low‐frequency decametric radio emission [ Menietti et al , 1998, 2001; Higgins et al , 2006]. The influence of Io's orbital position on Jupiter's radio emission has long been known [ Bigg , 1964].…”
Section: Introductionmentioning
confidence: 99%
“…Europa, Ganymede and Callisto also control jovian decametric radiation, although to a lesser degree than Io (Menietti et al 1998(Menietti et al , 2001, and Ganymede and Europa also cast auroral footprints. The unipolar inductor model is also applicable to systems where Jupiter is replaced by a magnetic white dwarf.…”
Section: Introductionmentioning
confidence: 99%